STABILITAS KINERJA REKSADANA SYARIAH DALAM MENGHADAPI GEJOLAK MAKRO EKONOMI - Arifin, M. Rahmawan; Nur, Muhammad Alan (Indonesian Journal of Islamic Literature and Muslim Society, 2019)
Islamic mutual funds as one of the financial investment products in Indonesia experienced rapid development in the last 5 years. Several studies have shown that the performance of a financial investment product is influenced by the macroeconomic conditions of a country. The purpose of this study is to determine the causality relationship and response of the performance of Islamic mutual funds in Indonesia when macroeconomic variables are simulated in an unstable state with an analytical approach using the Vector Error Correction Model (VECM). Observations in this study were made monthly from 2015-2019. The dependent variable in this study is the Net Asset Value (NAV) of Sharia Mutual Funds as a reference to the performance of Sharia Mutual Funds in Indonesia, while the macroeconomic variable as an independent variable consists of the money supply, inflation, central bank interest rates, the rupiah exchange rate, and stock indexes sharia in Indonesia. The results of this study note that simultaneous macroeconomic variables in Indonesia affect the performance of Sharia Mutual Funds in Indonesia.